Comparison of essential oil compositions of fresh and dried fruits of Magnolia kobus DC. - Kandhasamy Sowndhararajan, Haeme Cho, Byoungsun Yu, Songmun Kim (Journal of Applied Pharmaceutical Science, 2016)
The aim of this work was to determine the volatile constituents of fresh and dried (shade dried) fruits of Magnolia kobus DC. using gas chromatography-mass spectrometry (GC-MS). Essential oils from fresh and dried fruits of M. kobus were obtained by steam distillation and the yields were 0.81 and 1.73% (v/w), respectively. GC-MS analysis revealed the identification of seventeen components from both the fresh and dried fruits of M. kobus, which were mostly monoterpene hydrocarbons (62.8–71.8%). A comparison of oils from fresh and dried fruits exhibited the changes in the amounts of several constituents. Major components of the essential oil were α-pinene (26.7–31.6%), β-pinene (20.2–27.9%) and limonene (8.6–10.0%). In the dried sample, concentration of α-pinene, β-pinene, caryophyllene, camphene, and α-humulene contents were decreased. On the other hand, limonene, α-terpineol, bornyl acetate and terpinen-4-ol contents were increased in the dried sample. The present investigation clearly suggested that the drying treatment decreased the concentration of major components in the essential oil of M. kobus fruit.
Keywords: Magnolia kobus, essential oil, fruit, dried.